The effects of short time hyperoxia on glutamate concentration and glutamate transporters expressions in brain of neonatal rats. (27th July 2021) - Zhao, Yuwei; Liang, Lei; Liu, Guanghui; Liu, Yongqing; Zheng, Hong; Dai, Liying
Highlights: We aimed to investigate the effect of short time hyperoxia on glutamate homeostasis and glutamate transporters expressions in immature brain. Hyperoxia induced glutamate accumulation in both immature cerebrum and cerebellum of neonatal rats.. Increased oxidative stress and decreased expressions of glutamate transporters including EAATs and VGLUTs within 2 weeks after hyperoxia challenge contributed to the disturbance of glutamate homeostasis in rat brain. Abstract: Preterm infants often suffer from impaired postnatal brain development, and glutamate excitotoxicity is identified as a pivotal mechanism of hyperoxia-induced neurological abnormality. We aimed to investigate the effect of short time hyperoxia on glutamate homeostasis and glutamate transporters expressions in immature brain. Six-day-old (P6) rat pups were exposed to 80% oxygen for 24 h (the hyperoxia group) or placed in atmospheric air (the control group). The concentrations of glutamate and γ-aminobutyric acid (GABA) in immature cerebrum and cerebellum at P7, P14 and P21 were determined by ELISA. The mRNA levels of glutamate transporters including excitatory amino acid transporter 1 (EAAT1), EAAT2, EAAT3, vesicular glutamate transporter 1 (VGLUT1) and VGLUT2 in brain were determined by qPCR. Glutamate accumulation was induced by hyperoxia both in immature cerebrum and cerebellum at P7 but got gradually attenuated at P14 and P21, as evidenced by the changes of glutamate and GABA concentrations. Hyperoxia also induced sustained glutamatic oxidative stress in both cerebrum and cerebellum, as GSH (reduced glutathione) levels in the hyperoxia group were constantly higher than the control group at three examined time-points. Furthermore, at P7, the expressions of all glutamate transporters decreased in both cerebrum and cerebellum except that of EAAT1. At P21, VGLUT2 in cerebrum and EAAT1, EAAT3 and VGLUT2 in cerebellum still displayed significant decrease in expression levels upon hyperoxia stimulation. Taken together, our results indicate that hyperoxia induces glutamate accumulation in brain of rat pups, which is associated with increased oxidative stress and decreased expressions of glutamate transporters.